h - Popescu, Delia, 1978-; ebrary, Inc. (Lanham, Md. : Lexington Books, 2012)
"This book explores the account of responsibility supported by the work of Vaclav Havel, anti-communist dissident, playwright, former President of the Czech Republic, and political thinker. Havel's work stands as a remarkable articulation of responsible action under the extreme circumstances of Eastern European totalitarianism, but the value of his inquiry extends beyond that time and place"--
Machine generated contents note: -- Acknowledgments Introduction Chapter One--The Choice to Write Chapter Two--Post-totalitarianism: Havel's New Concept of Power Chapter Three--The Bridge of Excuses: Unraveling Identity in Havel's Plays Chapter Four--Between Modernity and Responsibility Chapter Five--The Breakdown in Tradition: Anti-politics in Havel's Political Thought Conclusion--The Dorian Gray Image of Modern Times Bibliography About the Author Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: x; x; Electronic books